Microtensile Bond Strength between Zirconia Core and Veneering Porcelain after Different Surface Treatments - Sakineh Nikzadjamnani; Simindokht Zarrati; Masomeh Rostamzadeh (Tehran University of Medical Sciences, 2017)
Objectives: The long-term clinical success of all-ceramic restorations requires sufficient bond strength between the veneering ceramic and substructure. The present study compared the effects of three methods of surface treatment on the microtensile bond strength of the veneering porcelain to zirconia. Materials and Methods: Twelve zirconia blocks were randomly divided into four groups of aluminum oxide (Al2O3) air abrasion, carbon dioxide (CO2) laser irradiation, erbium-doped yttrium aluminum garnet (Er:YAG) laser irradiation, and control samples (no surface treatment). After surface treatment, the zirconia blocks were veneered with porcelain. To assess the surface topographies, four surface-treated specimens were left uncoated. Microtensile bond strength was tested in each group and was statistically analyzed by one-way ANOVA and post-hoc Tukey's test. Surface topographies were examined by using scanning electron microscopy (SEM). Results: The highest and lowest microtensile bond strength values were recorded in the Al2O3 (43.6±10.0 MPa) and control groups (34.7±8.2 MPa, P<0.05). The bond strengths in the CO2- and Er:YAG-irradiated groups were equal to 40.4±6.5 MPa and 38.2±7.5 MPa, respectively. The majority of the failures (mean=92.44%) were of cohesive nature located in the veneer, followed by mixed fractures (mean=7.6%). The milling marks of the computer-aided design/computer-aided manufacturing (CAD/CAM) machine were apparent in the control samples, while desert-like micro-cracks were observed on the surfaces treated with CO2 and Er:YAG lasers. Al2O3 air abrasion produced the roughest topography. Conclusions: Al2O3 air abrasion resulted in a higher microtensile bond strength compared to CO2 or Er:YAG laser irradiation. Cohesive failure mode was predominant. No pure adhesive failures were observed.